The influence of organizational culture and work ethics on the productivity of private high school teachers in Mataram - Sahat T Simorangkir (Institute of Computer Science (IOCS), 2023)
The purpose of this study is to determine the impact of organizational culture and work ethics on the labor productivity of Private Secondary School Teachers (SMAs) in Mataram City for the 2021-2022 school year. The study was conducted during the odd-numbered seasons of 2021-2022. The research method used is a questionnaire. The study population consisted exclusively of private high school teachers in Mataram city. Respondents were selected by a simple random her sampling technique and included a total of 125 teachers. The analysis results of this study showed that: (1) A simple correlation analysis showed a correlation coefficient of 0.575 and a path coefficient value of 0.422. This value indicates that organizational culture has a strong impact on teacher productivity. (2) A simple correlation analysis between work ethics and teacher productivity yielded a correlation coefficient of 0.541 and a path coefficient value of 0.363. This value indicates that work ethic has a strong impact on teacher productivity.